Health status and heat preparation at a UCI World Tour multistage cycling race - Périard, J. D.; Wilson, M. G.; Tebeck, S. T.; Stanley, J.; Girard, O. (Journal of Science and Medicine in Sport, 2024)
Objectives To assess health status and heat preparation of cyclists at the 2019 Tour Down Under and determine the alignment of heat mitigation strategies with current recommendations.